Stjepan Radić in republikansko gibanje v Sloveniji - Berberih-Slana, Aleksandra (Zgodovinski časopis, 2004)
After the 1923 election to the National Parliament, in which Stjepan Radić's HRSS (Croatian Peasant Party) was successful also in Slovenia. Radić continued to advocate and spread the republican movement among the Slovenes. After a disagreement with Anton Novačan, his former colleague, he started to search for new allies who could help him with the organization of his republican party. Hoping to reach an agreement and continue to cooperate with Radić, the Slovene People's Party suffered several disappointments. Not wishing to relinquish his independent status on the Slovene political scene, Radić posessed an additional threat to the Slovene's People's Party before the 1925 election to the National Parliament. Stjepan Radić was preparing his election strategy with the help of his new supporter, Albin Prepeluh, who had tried with his autonomistic ideas to persuade the Slovene People's Party to closely cooperate with Croatians; later on, Prepeluh himself established close contacts with the Croatian Peasant Party. Even though the leadership of the Croatian Peasant Party was against any cooperation with Prepeluh, wishing to maintain good relations with the Slovene People's Party, Stjepan Radić ignored their opinion. As seen from the printed media of that time the views within the Croatian Peasant Party were often different. While the Party's leadership advocated cooperation with the parties of the opposition and mutual support during the election period, Stjepan Radić prepared for the upcoming election with the help of his Slovene supporters, but without the Slovene People's Parthy. In views of this, the relations between the two parties became increasingly worse, and the chances for possible cooperation diminished. Winning three seats in the National Parliament in the 1925 election, Radič's ticket was a marked success in Štajersko; Prepeluh, on the other hand, was not successful in the district of Ljubljana. This was yet another proof that the voters had been attracted by the personality of Stjepan Radić himself, but far less by his party's political program
Keywords: history; zgodovina; republikansko gibanje; election; volitve; politična zgodovina; Croatia; Hrvaška; Slovenia; Slovenija; politične stranke; political party